Enhanced and Constant-value Transient Diffraction Efficiency from a Recorded Grating in a BaTiO3 Crystal - Sharif, S. M.; Ogusu, K. (Journal of Scientific Research, 2011)
A simple method has been proposed here to get an enhanced and constant-value transient diffraction efficiency for a large time scale from a recorded grating in an undoped BaTiO3 crystal. After writing a steady-state grating by two cw recording beams (λ=514.5 nm), when the recording beams are switched off, the recorded grating as well as the diffraction efficiency decreases at a faster rate initially, and thereafter reaches to almost a stationary level for some few seconds. The diffraction efficiency for this level is very small compared to that for a steady-state grating and it becomes smaller slowly with time. We can increase (about twice the initial stationary-level value) this small diffraction efficiency from its any initial value and have this value (increased) constantly for a large time scale by using a suitable backward-pulsed reading beam containing the same properties as the recording beams. Keywords: Photorefractive effect; Transient diffraction efficiency; Steady-state volume grating; Ferroelectric perovskite crystal. © 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi:10.3329/jsr.v3i2.5593 J. Sci. Res. 3 (2), 217-224 (2011)